PENGARUH KEMUDAHAN PENGGUNAAN DAN RISIKO PADA APLIKASI INVESTREE TERHADAP KEPUTUSAN BERTRANSAKSI MENGGUNAKAN FINANCIAL TECHNOLOGY (FINTECH) PEER TO PEER LENDING SYARIAH - Fadhila Ihsan Nursyahida (Al-Muamalat: Jurnal Ekonomi Syariah, 2021)
Digital technology is currently developing very rapidly, many new innovations have emerged in the field of technology ranging from hardware to software and even other supporting devices. Digital technology has also developed, supported by the increasing use of the internet and gadgets, from the financial service operating system, which has now undergone changes. Many financial service operating systems based on digital technology have emerged that can assist the activities and needs of the community. This study aims to determine how much influence the ease of use (Ease of Use), and risk on the Investree Application on the decisions of students who transact in using Financial Technology (Fintech) Peer to Peer Lending Syariah simultaneously. The research uses quantitative research methods, for the quantitative method is multiple test with a sample of 77 respondents. Questionnaire data collection was carried out as a data collection technique, for data processing assisted by using SPSS version 26 analysis tool. The results of the study based on the data obtained showed that the results of the Ease of Use variable had a significance value of tcount of 5.702 > ttable = 1.9917 or sig = 0.000 < = 0.05, meaning that Ha is accepted so that there is an influence of the ease of use of the Investree application on the decision to transact using Financial Technology (Fintech) Peer to Peer Lending Syariah, so it has a positive effect. The risk variable from the t test results with an alpha value of 0.05 then HO is accepted and Ha is rejected, because t = 1.696 < t-table = 1.9917 or sig = 0.094 > = 0.05 then there is no effect of risk on transaction decisions using Peer to Peer Lending Syariah, therefore it can ensure that the risky variable is negative and significant to the decision to transact using Financial Technology (Fintech) Peer to Peer Lending Syariah. The R² value has a value of 0.642, so it can be stated that the ease of use and risk in the Investree application affect the decision to transact using Sharia peer to peer lending financial technology (Fintech) together by 41.2%.